2018
DOI: 10.1007/s00441-018-2879-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived versus adipose-derived stem cells in wound healing: value and route of administration

Abstract: The stem cells with their distinct ability of self-renewal and differentiation are considered an innovation in wound healing. However, there is lack of studies comparing the differential effect of the type and administration route of stem cells in the wound healing context. Thus, the current study has been designed to elucidate the effect of two of the most important stem cell types-the bone marrow-derived and adipose-derived stem cells in full thickness wound healing-and to evaluate, in this optimized wound m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 99 publications
0
21
0
Order By: Relevance
“…It is indicated that MSCs from placental amnion, chorion, and umbilical cord exert similar beneficial effects on wound closure and neovascularization [28], and bone marrow, adipose tissue, and dental pulp are also proved to serve as a universal MSC source for burn wound healing [29]. Conversely, Aboulhoda and Abd El Fattah demonstrated that ADSCs show statistically significant improvement in wound healing than BMSCs [30]. And adipose-derived MSCs are also proved to exhibit greater angiogenic potential in comparison with BMSCs [31] and UCMSCs [22].…”
Section: Discussionmentioning
confidence: 99%
“…It is indicated that MSCs from placental amnion, chorion, and umbilical cord exert similar beneficial effects on wound closure and neovascularization [28], and bone marrow, adipose tissue, and dental pulp are also proved to serve as a universal MSC source for burn wound healing [29]. Conversely, Aboulhoda and Abd El Fattah demonstrated that ADSCs show statistically significant improvement in wound healing than BMSCs [30]. And adipose-derived MSCs are also proved to exhibit greater angiogenic potential in comparison with BMSCs [31] and UCMSCs [22].…”
Section: Discussionmentioning
confidence: 99%
“…Digital images were uniformly acquired and snapped at x400 magnification by Olympus IX51 equipped with a DP72 device camera. The obtained data were calculated in six non‐overlapping fields per slide in each group 44 …”
Section: Methodsmentioning
confidence: 99%
“…All antibodies were purchased from Abcam ® (Cambridge). The color reaction was then made with HRP‐linked polymer detection system and counterstained with hematoxylin as previously described 29 . Paraffin‐embedded mouse spleen tissue was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%